AEMFC Exploiting a Pd/CeO2-Based Anode Compared to Classic PEMFC via LCA Analysis - Simone Minelli; Michele Civelli; Sandra Rondinini; Alessandro Minguzzi; Alberto Vertova (Hydrogen, 2021)
The hydrogen economy relies on effective and environmentally friendly processes for energy conversion and storage. To this end, hydrogen is progressively holding the role of preferred energy vector. Within this frame, electrochemical science and technology is actively contributing in developing advanced fuel cells and water electrolyzers to be integrated in (i) energy parks to decouple production and consumption; (ii) exploit renewable sources; (iii) favour the progressive reduction of fossil fuels and reduce the greenhouse effect via decarbonization. The exploitation of the relevant processes and devices call for the sound control over the environmental impact from production to end-of-life steps. Here, life-cycle analyses were performed and discussed focusing on both acid and alkaline fuel cells, i.e., proton exchange membrane fuel cells (PEMFC) and anion-exchange membrane fuel cells (AEMFC), and assessing their contribution to key environmental impact categories such as, for example, global warming and ozone layer depletion. Within these premises, the study points to the benefits of replacing platinum by low load Pd/CeO2 bifunctional electrocatalyst on electrochemical hydrogen production and usage.